2021
DOI: 10.1177/0192623320985045
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Specific Biomarkers of Chronic Renal Injury and Their Potential Application in Nonclinical Safety Assessment Studies

Abstract: A host of novel renal biomarkers have been developed over the past few decades which have enhanced monitoring of renal disease and drug-induced kidney injury in both preclinical studies and in humans. Since chronic kidney disease (CKD) and acute kidney injury (AKI) share similar underlying mechanisms and the tubulointerstitial compartment has a functional role in the progression of CKD, urinary biomarkers of AKI may provide predictive information in chronic renal disease. Numerous studies have explored whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 442 publications
(683 reference statements)
0
19
0
Order By: Relevance
“…The global study of these markers can provide us with important information about the muscular state of the individual, even if each marker can separately be a classic marker of another pathology. Thus, albumin and creatinine are typical markers of kidney damage 18 . Furthermore, the albumin and sodium decreases observed in DP with clear downward trends in glucose and detected total proteins are also clear indicators of malnutrition and poor intestinal absorption, 19 which have a devastating effect on muscles and promotes protein catabolism that further accelerates muscle wasting, and recent articles support their role as a warning signal in elderly people 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The global study of these markers can provide us with important information about the muscular state of the individual, even if each marker can separately be a classic marker of another pathology. Thus, albumin and creatinine are typical markers of kidney damage 18 . Furthermore, the albumin and sodium decreases observed in DP with clear downward trends in glucose and detected total proteins are also clear indicators of malnutrition and poor intestinal absorption, 19 which have a devastating effect on muscles and promotes protein catabolism that further accelerates muscle wasting, and recent articles support their role as a warning signal in elderly people 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the albumin and sodium decreases observed in DP with clear downward trends in glucose and detected total proteins are also clear indicators of malnutrition and poor intestinal absorption, 19 which have a devastating effect on muscles and promotes protein catabolism that further accelerates muscle wasting, and recent articles support their role as a warning signal in elderly people 20 . Creatinine, in turn, is filtered out of the blood by the renal glomeruli, so increased blood levels of creatinine are often used as an indicator of renal dysfunction 18 . However, creatinine is also a breakdown product of creatine phosphate in muscle, and as a waste product of muscle metabolism, 21 it is released into the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in this study serum SDMA and creatinine were found to provide complimentary information on renal function, SDMA has been found to be a more sensitive renal function biomarker than serum creatinine when evaluated in the context of naturally occurring chronic kidney disease in humans and animals [8,[10][11][12]. A recent review of chronic renal injury biomarkers for nonclinical safety assessment highlighted SDMA as one of the most promising candidates for a chronic renal biomarker, and evaluation of SDMA in future nonclinical study designs is warranted to better define performance of this biomarker with regard to time-course, species, as well as type and extent of renal injury [37]. Interestingly serum SDMA and creatinine were both more responsive than the tubular injury markers KIM-1 and CLU for identification of gentamicin-induced renal toxicity in the 4-dose treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that more research is needed to determine the accuracy of GFR estimations; these research efforts may include more precise assessments of novel filtration markers [20,21]. In the meantime, clinicians should keep in mind the limitations of using currently available equations.…”
Section: The Concept Of the Estimation Of Glomerular Filtration Rate ...mentioning
confidence: 99%